Electricity Price Increases and Energy Demand: The Case of an Electricity Supplier in South Africa - Nkosi, N. S.; Govender, Krishna K. (International Journal of Energy Economics and Policy, 2022)
South Africa (SA) experienced electricity supply and demand challenges since the first load shedding crisis in 2008, which also resulted in drastic price increases during the period 2009 - 2018. This study aimed to investigate the impact of price increases on the demand for electricity supplied by one of South Africa’s largest electricity supplier in Johannesburg, South Africa, namely, City Power. An on-line survey was conducted using QuestionPro, to collect data from a random sample of 107 respondents stratified as residential, commercial and industrial customers. Although the impact of the electricity price increases differed across customer segments, all customers were of the view that energy conservation is necessary to protect the national grid from total collapse. A key finding was the interest shown by the different customer segments in investing on renewable and alternate energy sources to counter the electricity price increases. Thus, City Power should invest in generating its own electricity to reduce over-reliance on Eskom which is the national state-owned electricity generator and supplier. City Power should also consider investing in renewable energy sources, but this will require the SA government to change current energy policies and guidelines.